2016
DOI: 10.1002/mame.201500413
|View full text |Cite
|
Sign up to set email alerts
|

Impressive Rate Raise of the Hydrosilation Reaction Through UV‐Activation: Energy and Time Saving

Abstract: Silicone materials are widely used in many fields such as electrical or food industries and their consumption is constantly growing. They are generally cured by vulcanization reaction for long time at high temperatures which requires high energy consumption. The possibility to achieve the polymerization of silicone rubbers by UV‐activation promotes the reduction of both time and temperature leading to an impressive energy saving. Indeed, this process is more than 30 times faster than the thermal one. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Hence, the photocatalytic hydrosilylation of electron-poor alkenes could be performed. The reactions could be Marchi and coworkers demonstrated in how far (in terms of energy and time saving) photo-activation is the favorable way for (crosslinking) hydrosilylation catalysis employing Pt II (acac) 2 as catalyst [91]. They used the catalyst for photo-and thermal activation and monitored the silane conversion at various temperatures.…”
Section: Light-initiated Hydrosilylation Reactionsmentioning
confidence: 99%
“…Hence, the photocatalytic hydrosilylation of electron-poor alkenes could be performed. The reactions could be Marchi and coworkers demonstrated in how far (in terms of energy and time saving) photo-activation is the favorable way for (crosslinking) hydrosilylation catalysis employing Pt II (acac) 2 as catalyst [91]. They used the catalyst for photo-and thermal activation and monitored the silane conversion at various temperatures.…”
Section: Light-initiated Hydrosilylation Reactionsmentioning
confidence: 99%
“…For better durability and reliability, they should be vulcanized to form a three‐dimensional crosslinked network via polycondensation at room temperature or hydrosilylation or peroxide reaction at high temperature . However, these curing methods have long been considered as a seriously time‐consuming and energy‐intensive process . Under the uptrend of sustainable development, UV‐curing or photopolymerization technology has recently attracted extensive interest because of its fast rate, high efficiency, energy conservation, and environmental friendliness …”
Section: Introductionmentioning
confidence: 99%
“…Herein, Pt(acac) 2 and (Me‐Cp)Pt(Me) 3 are the predominant cases. It has demonstrated that the photopolymerization rate of hydrosilylation catalyzed by Pt(acac) 2 is 30‐fold faster than thermopolymerization, while (Me‐Cp)Pt(Me) 3 complex presents a much higher photochemical reactivity than Pt(acac) 2 . However, the photopolymerization mechanism and kinetics of photoactivated hydrosilylation has not been clearly disclosed.…”
Section: Introductionmentioning
confidence: 99%
“…Silane‐ene chemistry has been proposed as a further potential candidate by implementing silanes with abstractable hydrogens. Additionally, such silanes are also of significant interest for photografting applications on silicon surfaces and in silicon polymer science . With the establishment of a working silane‐ene system, radical oxygen inhibition could possibly be prevented .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, such silanes are also of significant interest for photografting applications on silicon surfaces [17] and in silicon polymer science. [18] With the establishment of a working silane-ene system, radical oxygen inhibition could possibly be prevented. [19] New reactive silanes could also be used as radical reducing agents [20] or type II coinitiators.…”
Section: Introductionmentioning
confidence: 99%